Pengaruh Konten Laman Pemerintahan Terhadap Reputasi Lembaga - Prisgunanto, Ilham; Pranawukir, Iswahyu (Universitas Islam Malang, 2020)
The world of information technology coming in 4.0 era, that why any company should be used internet networking for communicated the people whom they serve. Open access models will descripe reformation in organizational birocracy in Indonesia especially for goverment reputation. Further research in this area may include netters reaction and attitude for government organization reputation. the Theoretical study in this research was uses and gratification theories and behavioral psychological. The metodological research uses positivistic paradigm and quantitative model. Sampel this research 92 respondens which all student in a campus in Jakarta. Finding research talk about there are low impact for information from Government’s website with attitude hanging netters for government reputation. Netters always look a website just in updating reporting informations. Beside it’s attitude netters for issues acquistion in medium level so website management must be make attractive for performance information.